Autoethnography as feminist method: Sensiting the feminist 'I' - Ettorre, Elizabeth (Routledge, 2018)
Autoethnography is an ideal method to study the ‘feminist I’. Through personal stories, the author reflects on how feminists negotiate agency and the effect this has on one's political sensibilities. Speaking about oneself transforms into stories of political responsibility - a key issue for feminists who function as cultural mediators.
Keywords: approches et analyses; corps; ethnographie; méthodologie; outils; ouvrages de références; point de vue situé; santé; thématiques

The Routledge handbook of gender and violence - Lombard, Nancy (Routledge, 2018)
The Routledge Handbook of Gender and Violence provides both a comprehensive and authoritative state-of-the-art overview of the latest research in the field of gender and violence. Each of the 23 specially commissioned chapters develops and summarises their key issue or debate including rape, stalking, online harassment, domestic abuse, FGM, trafficking and prostitution in relation to gender and violence. They study violence against women, but also look at male victims and perpetrators as well as gay, lesbian and transgender violence. The interdisciplinary nature of the subject area is highlighted, with authors spanning criminology, social policy, sociology, geography, health, media and law, alongside activists and members of statutory and third sector organisations. The diversity of perspectives all highlight that gendered violence is both an age-old and continuing social problem. By drawing together leading scholars this handbook provides an up-to-the-minute snapshot of current scholarship as well as signposting several fruitful avenues for future research. This book is both an invaluable resource for scholars and an indispensable teaching tool for use in the classroom and will be os interest to students, academics, social workers and other professionals working to end gender-based violence.
Keywords: approches et analyses; communication; cours; criminologie; discipline; droit; géographie; justice sociale; outils; ouvrages de références; premier cycle; rapports sociaux de sexe; ressource en ligne; santé; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; sofia; thématiques; travail; violences